Wpływ sytuacji decyzyjnej na przebieg procesu podejmowania decyzji strategicznych - Jankowska-Mihułowicz, Marzena (The impact of decisive situation on the strategic decision making process, 2006)
In this paper the decisive situation was characterized, which is accompanied by strategic decisions made in the organization. The impact of uncertainty, complexity and dynamic decisive situation on strategic decision making process was shown. Moreover the process was defined taking into consideration individual dimensions of decisive situation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 63-71